PENGARUH KEPERCAYAAN DAN SERVANT LEADERSHIP TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (STUDI KASUS PADA DINAS PERIKANAN DAN PETERNAKAN KABUPATEN BLORA) - Oktiani Windar Kristianti; Fitri Lukiastuti (Magister Manajemen STIE Bank BPD Jateng, 2021)
Service can be defined as the process of providing services (serving) the needs of people or communities who have an interest in the organization in accordance with the main regulations and procedures that have been previously determined. Seeing the importance of employees in an organization, employees need more serious attention to the tasks they are doing so that the results of the organization will be achieved maximally. Through high servant leadership, employees will work harder in carrying out their jobs. This study was to determine the effect of Trust and Servant Leadership on Performance with the mediation of Organizational Citizenship Behavior (OCB) for case study employees at the Fisheries and Livestock Service Office of Blora Regency with 50 respondents. The data collection technique used a questionnaire. The results of the study using the equation path analysis and sobel test to determine the mediation ability of OCB to performance. The results showed positive results of Trust, Servant Leadership to Performance and OCB were able to mediate Trust and Servant Leadership to employee performance..